ln(8x)=2ln(6x)

Simple and best practice solution for ln(8x)=2ln(6x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for ln(8x)=2ln(6x) equation:


Simplifying
ln(8x) = 2ln(6x)

Remove parenthesis around (8x)
ln * 8x = 2ln(6x)

Reorder the terms for easier multiplication:
8ln * x = 2ln(6x)

Multiply ln * x
8lnx = 2ln(6x)

Remove parenthesis around (6x)
8lnx = 2ln * 6x

Reorder the terms for easier multiplication:
8lnx = 2 * 6ln * x

Multiply 2 * 6
8lnx = 12ln * x

Multiply ln * x
8lnx = 12lnx

Solving
8lnx = 12lnx

Solving for variable 'l'.

Move all terms containing l to the left, all other terms to the right.

Add '-12lnx' to each side of the equation.
8lnx + -12lnx = 12lnx + -12lnx

Combine like terms: 8lnx + -12lnx = -4lnx
-4lnx = 12lnx + -12lnx

Combine like terms: 12lnx + -12lnx = 0
-4lnx = 0

Divide each side by '-4'.
lnx = 0

Simplifying
lnx = 0

The solution to this equation could not be determined.

See similar equations:

| -x^2+6*x-8=0 | | -2(9v-4)+2v=2(v+7) | | x^2-9*x-22=0 | | 2x^2+8x+9= | | x^2+10x=2x-6 | | 7(9x+2)=8p | | -6(-4u+6)-2u=4(u-6)-6 | | X+2000=4x-1000 | | x^2-4*x+3=0 | | 3g+8=5g-20 | | 5(x-20)=3(x+30) | | 17x-6=3x+64 | | 4(x-2)-7x=7 | | x^2+12*x+20=0 | | 7.6X-2.2=54 | | 2(x+10)+3(x+20)=180 | | (11x+21)=(7x+33) | | x+(x+2)=790 | | -9(2)= | | 5(x+4)=3(x+20) | | 2x^2+20x-24=0 | | 2(x-7)=64 | | 5*(2x+3)=8x-6 | | 10x+8-5x-3=85 | | 42p^2-85p+42=0 | | 5(x+4)=90 | | 7xy+2y^2=0 | | -t^2+4=0 | | 5x^2-36w=32 | | 4x+6+6x+8=94 | | -1x+4y=4 | | e-t^2+4=0 |

Equations solver categories